Sort by

- Relevance
- |Time

... an ellipse with major axis parallel to the y-axis, the foci are (h,

**k**-**c**) and (h,**k**+**c**) where c = √(b² - a²) In this case, c = √(...1 Answers · Education & Reference · 13/05/2019

C = (F - 32)/1.8 => C = (105 - 32)/1.8 ≈ 40.56 C = (-25 - 32)/1.8 ≈ -31.7 C = K - 273.15 =>

**K**=**C**+ 273.15 K = 40.56 + 273.15 = 313.71 K = -31.7 + 273.15 = 241.451 Answers · Education & Reference · 31/12/2016

... (h,k±a) linear eccentricity c = √(a²+b²) foci (h,

**k**±**c**) eccentricity e = c/a I think (but am not certain) that the ...1 Answers · Education & Reference · 03/05/2016

... <-> cC + dD And then equilibrium constant

**K**= ([**C**]^c * [D]^d) / ([A]^a * [B]^b)2 Answers · Education & Reference · 11/03/2016

...let c = the speed of the current downstream, the kayak travels at the rate of (

**k**+**c**) upstream, the kayak travels at the rate of (**k**-**c**) Distance = 30...2 Answers · Education & Reference · 21/05/2015

p v / t = p v / t 1.12 * 15.7 / 245 = 1.67 * 11.2 / t t = (1.67 * 11.2 * 245) / (1.12 * 15.7)

2 Answers · Education & Reference · 15/05/2015

...should be the constant "e" The general exponential form, where A,

**K**,**C**and b are constants is: y = A...1 Answers · Education & Reference · 23/04/2015

binomial distribution with n = 10, p = 0.02, q = 0.98 formula P(

**k**) =**C**(n,k) *p^k *q^(n-**k**),**C**(n,k) = n!/(k!(n-k)!) P(0) = C(10,0...1 Answers · Education & Reference · 15/10/2014

That means the discriminant, b^2 - 4ac, comes out zero. a = 1 b =

**k****c**= 67 k^2 - 4•1•67 = 0 k^2 - 268 = 0 so k = ± √2681 Answers · Education & Reference · 21/09/2014

**K**=**C**+ 273 or C = K - 273 C = 373 - 273 = 1001 Answers · Education & Reference · 19/08/2014

##### Ads

related to**K.C**